2017
DOI: 10.1177/0009922817729484
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Function Testing in Neonates With Maternal History of Disease

Abstract: Maternal history of thyroid disease can cause congenital hypothyroidism due to thyroid-stimulatng hormone (TSH) blocking antibodies. No guidelines exist regarding testing beyond the newborn screen. TSH and T4 levels exhibit significant fluctuations after birth which complicates testing. A total of 561 newborns with thyroid function testing done for maternal history of thyroid disease in the newborn nursery were identified retrospectively via chart review, and thyroid disease status was assessed in 352. Newborn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 14 publications
2
11
0
2
Order By: Relevance
“…History of thyroid problems in mothers or fathers of newborns with CH is considered a risk factor for CH in the general population, 9 with a clear relationship between FHTD and CH being observed. In the study by Underland et al 21 , however, said association was found only in a bivariate analysis, and a positive FHTD was restricted only to the parents. Although the exact explanation for the association between FHTD and CH remains unknown, autoimmune pathogenesis seems unlikely.…”
Section: Discussionmentioning
confidence: 85%
“…History of thyroid problems in mothers or fathers of newborns with CH is considered a risk factor for CH in the general population, 9 with a clear relationship between FHTD and CH being observed. In the study by Underland et al 21 , however, said association was found only in a bivariate analysis, and a positive FHTD was restricted only to the parents. Although the exact explanation for the association between FHTD and CH remains unknown, autoimmune pathogenesis seems unlikely.…”
Section: Discussionmentioning
confidence: 85%
“…La historia de problemas tiroideos en madres o padres de RN con HC se considera un factor de riesgo para HC en la población general, 9 evidenciando una clara relación entre la HFET y el HC. En el estudio de Underland et al 21 , sin embargo, dicha asociación se encontró solo en un análisis bivariante y la HFET positiva fue confinada solo a los padres. Aunque la explicación exacta de la asociación entre la HFET y el HC permanece sin conocerse, la patogénesis autoinmune parece poco probable.…”
Section: Discussionunclassified
“…En lactantes no malformados, menos del 3 % de los casos con HC resultan de enfermedad materna autoinmune relacionada con anticuerpos que inhiben la TSH. 8,21 En nuestro estudio no se evaluó la etiología autoinmune, pero parece también improbable que esta explique la asociación entre la HFET y el HC en nuestros neonatos con SD, ya que solo uno de los lactantes estudiados con HC tuvo una madre hipotiroidea. En cualquier caso, la agregación familiar de enfermedad tiroidea pone en evidencia una predisposición genética para HC en SD, pero requerirá obligatoriamente su confirmación posterior, incluyendo su evaluación usando otros marcadores genéticos.…”
Section: Discussionunclassified
“… 9 - 13 Other recent studies have demonstrated utility in additional testing in the newborn period, although optimal timing of testing has not been determined. 1 , 3 , 6 , 8 , 14 Additional testing obtained unnecessarily has a significant impact on resource allocation and referrals; moreover, TFTs obtained too early after birth may be affected by the newborn’s physiologic thyroid-stimulating hormone surge and therefore yield false positive results. 8 , 14 This topic is controversial, as some amount of additional testing may be considered acceptable to ensure a diagnosis with preventable developmental implications is not missed.…”
Section: Discussionmentioning
confidence: 99%
“…There are currently no guidelines for obtaining additional testing in infants with maternal hypothyroidism apart from the newborn screen, and current literature has yielded mixed results on the topic. 1 , 3 , 8 - 14 Therefore, the question of whether additional screening apart from the newborn screen is warranted in these cases and the optimal timing to do so is controversial.…”
Section: Introductionmentioning
confidence: 99%